Evaluation and optimization of the potential of a handheld Raman spectrometer: in situ, noninvasive materials characterization in artworks. (25th March 2019) - Pozzi, Federica; Basso, Elena; Rizzo, Adriana; Cesaratto, Anna; Tague, Thomas J.
Abstract: Decades of technological and methodological advances in Raman spectroscopy have brought this technique from laboratory innovation to a well‐established analytical tool with increasing applicability to the study of cultural heritage objects. Enduring research in the field of miniaturization has given rise to new generations of mobile, portable, and handheld spectrometers that have deeply transformed the way in which scientists approach materials analysis. Although sometimes limited in terms of performance and flexibility compared with their benchtop counterparts, miniaturized instruments are typically compact and light, user‐friendly, and equipped with fiber optics and batteries, thus enabling the operator to easily transport them and collect data in the field in a timely manner. In this work, a new handheld Raman spectrometer was evaluated for the in situ, noninvasive analysis of organic and inorganic materials in artworks from five prestigious New York City museums. Relevant examples include the following: the investigation of indigotin‐containing plant dyes in Romano‐Egyptian funerary portraits from the Brooklyn Museum; the detection and identification of natural blue colorants and mineral pigments in Medieval and Renaissance manuscripts from The Morgan Library & Museum; the study of a yellow pigment and a proteinaceous inlay material on a 12th‐century Korean lacquered box in the collection of The Metropolitan Museum of Art; the characterization of synthetic organic dyes and pigments used by Henri Matisse in one of his cutouts belonging to The Museum of Modern Art; and the identification of different plastics, fillers, and pigments in a work by Jeff Koons in the holdings of the Whitney Museum of American Art. Abstract : The present study demonstrates the potential of handheld Raman spectroscopy for the in situ, noninvasive analysis of cultural heritage objects that cannot be sampled or moved from museums' galleries, storages, or conservation studios. Works of art investigated belong to five prestigious New York City museums, span 1, 900 years, and are representative of various cultures. Materials characterized include natural plant dyes, traditional mineral colors, modern synthetic organic pigments, as well as proteinaceous materials, plastics, and fillers.